OP0116 Switch from non-radiographic to radiographic axial spondyloarthritis is highly dependent of baseline objective signs of inflammation: 5 year data of the desir cohort. (15th June 2017) - Dougados, M; Sepriano, A; Molto, A; Ramiro, S; Hooge, M De; Berg, R Van Den; Compan, V Navarro; Mattei, C De; LandewΈ, R; Heijde, D Van Der
Abstract : Background: The natural history (e.g. appearance of structural damage) of non-radiographic (nr) axial (ax) Spondyloarthritis (SpA) is not well known. Objectives: To evaluate the switch from nr- to radiographic (r) status of recent onset axSpA after 5 years of follow-up and its predisposing factors. Methods: Patients: Recent onset axial SpA (DESIR Cohort). Outcome measure: Radiographic SIJ status according to the mNY criteria after 5 years follow-up. Reading of the SIJ-X-Rays: 3 trained readers unaware of the chronology of the films. Potential predisposing factors: Demographics, smoking status, HLA-B27, Bone Marrow Edema (BME) at MRI of the SIJ, CRP, disease activity and treatment. Statistical analysis: The radiographic progression has been evaluated in both the completers and after Linear Extrapolation (LE) and Last Observation Carried Forward (LOCF) technique in case of missing data. The predictive factors of radiographic progression were evaluated on the completer population using multilevel binomial GEE analysis incorporating measurements from all readers at 5-years and taking into account the within-reader correlation.Moreover, the progression rate was assessed in subgroups of patients according to CRP status and MRI-SIJ status at baseline. Results: At baseline, 62 out of the 416 patients (14.9%) were considered r-ax-SpA. Out of these 416 patients, 24 (5.8%) changed from mNY negative to mNY positive after 5-years. Conversely, 3 patients changed from mNY positive at baseline to negative at year 5 (e.g. 0.7%) resulting in a net progression of 5.1%. These results were similar when applying LOCF and LE (4.1% and 3.8% net progression). In the multivariate analysis, presence of BME at MRI-SIJ was highly predictive of radiographic progression (OR=4.85 [95% CI: 2.95–7.97]) together with a younger age (OR=0.97 [95% CI: 0.94–0.99]) and longer symptom duration (OR=1.40 [95% CI: 1.04–1.89]). Of the 383 patients with complete data, the net % patients who switched from nr-axSpA to r-axSpA after 5 years ranged from 2.0% to 13.5% according to the presence of objective signs of inflammation at baseline (see figure). Conclusions: This is the first cohort in early axSpA with 5-year follow-up demonstrating the importance of presence of objective signs of inflammation as predisposing factors of development of radiographic sacroiliitis. Disclosure of Interest: None declared